Development and Validation of Parental Support Scale of Children’s Sports Training in China: Socio-Ecological Approach - Zheng, Nan; Yang, Ye (Frontiers in Psychology, 2022)
Objectives To promote Chinese children participation in sports training and acquisition of sports skills, we combined a social ecological research framework with parental support to develop the Parental Support for Children’s Sports Training Scale (PSCSTS). Methods The scale was initially developed based on literature review, group interviews, and expert evaluations. A complete reliability and validity test was conducted on 1,594 parents of primary and secondary schools in Shanghai. Results The PSCSTS has 37 questions, and exploratory factor analysis has formed 10 factors: policy support, parents’ financial support, community support, media support, sports development, school activity participation, parents’ exercise habits, training quality support, development of school sports activities, learning skills. The higher-order models constructed by validated factor analysis fit well (χ2/df = 2.130, RMSEA = 0.038, SRMR = 0.042, GFI = 0.911, CFI = 0.928). The Parents of children of different sexes have measurement invariance in the PSCSTS. Conclusion The PSCSTS developed in this study based on a social-ecological framework has high reliability and validity, and can be used as a comprehensive measure of parental support for their children’s sports training.